Estudo do comportamento geoquímico do cromo (III) e (VI) no solo - Ramos, Raquel Lima [UNIFESP] (2015)
Chromium is found in the environment in two oxidation states, the trivalent form and hexavalent. The first, in trace concentrations, is considered an essential nutrient for plants and animals; already the second, is toxic and carcinogenic at any concentration. In case of contamination by industrial waste from chrome both forms can interact with the constituents of the soil. This study aims to analyze the geochemical behavior of chromium (III) and (VI) in Oxisol, in order to assist in choosing the best remediation method of areas contaminated by this ion. The Rhodic was chosen because it has a wide geographic distribution in Brazil. This soil was characterized chemical, physical and mineralogical before being used in the removal tests on Cr (III) solution and (VI) and incubating these ions directly in the soil for up to 30 days. Then the soil samples used in chromium removal were analyzed by sequential extraction to verify the metal layers interact with the main soil. It was observed that the analyzed surface comprised of quartz, kaolinite, goethite, hematite and gibbsite, has acid pH (4.3), point of zero charge (PZC) equal to 3.6; organic matter content of 4.6% and cation exchange capacity (86.6 mmol dm-3) high (to have been collected on the horizon). It was found that the original conditions of the soil, there was a greater removal of Cr (III) solution of Cr (VI) due to their preference for adsorbing cations (verified by CEC data, and pH PZC). Removal of Cr (VI) in solution from the soil in solution only increased with longer periods (between 10 and 30 days), probably caused by the change (reduction) of the metal to the trivalent form and whose reaction in soil conditions is very slow. The removal efficiency of Cr (VI) only by the soil increased with decrease in pH due to increased reduction reaction by the organic material to be favored in these media. However, due to the predominance of negative charges on soil particles, of the Cr3 + solution remained. On the other hand, in systems where Cr (III) and (VI) remained incubated in soil, it was observed that virtually all Cr (VI) was reduced to the trivalent form, from the beginning of the test. The data from sequential extraction analysis indicated that chromium (total) is preferably associated with organic matter, followed by mineral oxides and iron hydroxides and the phase exchangeable soil. Chromium associated with this last stage corresponds to the bioavailable fraction, depending on its concentration (greater than 10 mg kg-1) can interfere with growth of plants, even in trivalent form. Tests using phytoremediation Impatiens Wallerian revealed that chromium is concentrated in the roots (possibly in trivalent form) because the Cr (VI) is a highly oxidizing agent. It is therefore the main constituents as soil, organic matter and minerals iron, can assist in the removal of Cr (VI), reducing their mobility and hence its toxicity to the environment.